Revealing the Structure and Biodiversity Patterns of Fish Communities in River Networks Based on Environmental DNA - Ziyu Liu; Yongsheng Wu; Wenhui You; Shuxin Li; Ge Shi; Chen Zhang (Fishes)
Revealing taxonomic, functional, and phylogenetic dimensions of biodiversity is critical for the effective conservation and management of aquatic organisms in freshwater ecosystems subjected to multiple threats. Fish biodiversity patterns in river ecosystems exhibit complex spatiotemporal variation influenced by hydrological connectivity and the dispersal ability of species within the river network. This study utilized eDNA metabarcoding to investigate fish communities in three subtropical mountain rivers, aiming to uncover the community structure and spatiotemporal dynamics of the multidimensional biodiversity of fish communities across varying positions within the river network. The three biodiversity indices of the fish communities at the confluence were significantly greater than those of the mainstream community in the dry season, whereas the phylogenetic diversity of the fish community at the tributaries during the wet season was significantly greater than that in the mainstream. This likely reflected the unique spatial configuration of confluences and the seasonal dispersal of fish in the river network. The results of this study highlighted the important role of confluences and tributaries in river networks and the fact that they need to be prioritized to conserve riverine fish diversity.